Sex-dependent epigenetic disruption of YY1 binding by prenatal BPA exposure downregulates Matr3 and alters Agap1 splicing in the offspring hippocampus - Pattanachat Lertpeerapan; Songphon Kanlayaprasit; Surangrat Thongkorn; Kasidit Kasitipradit; Pawinee Panjabud; Kwanjira Songsritaya; Thanawin Jantheang; Masanobu Morita; Takaaki Akaike; Valerie W. Hu; Depicha Jindatip; Thanit Saeliw; et al. (Biology of Sex Differences)
Abstract Background Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by impairments in communication, social interaction, and behavior. Its etiology involves a combination of genetic and environmental factors, and it is more prevalent in males. Bisphenol A (BPA), an endocrine-disrupting chemical commonly found in plastics, has been linked to an increased risk of ASD. However, the molecular mechanisms by which BPA affects gene regulation remain poorly understood. Methods In this study, hippocampal tissues were collected from rat offspring prenatally exposed to BPA at a dose of 5,000 µg/kg of maternal body weight, equivalent to the NOAEL. RNA sequencing was performed to identify genes exhibiting differential alternative splicing. ASD-related alternatively spliced genes were selected for validation using high-resolution melting (HRM) analysis. Ingenuity Pathway Analysis (IPA) was used to predict associated biological functions, diseases, and molecular interaction networks. Additionally, BPA-responsive transcription factors, RNA-binding proteins, splicing regulators, and differentially expressed genes were analyzed to identify upstream regulatory mechanisms. Gene expression was validated by qRT-PCR, and transcription factor binding was confirmed via chromatin immunoprecipitation-qPCR (ChIP-qPCR). Results RNA-seq analysis revealed that prenatal BPA exposure altered the alternative splicing of ASD-related genes in the hippocampus, including Agap1, Ap2b1, and Kifap3. Gene ontology and pathway analyses indicated that differentially spliced genes were involved in mRNA splicing processes in males and neuronal functions in females, patterns that align with ASD-related phenotypes. ChIP-qPCR revealed sex-specific differences in YY1 transcription factor binding at the Matr3 promoter, with males showing reduced binding, leading to downregulation of Matr3 expression. Notably, Agap1, a target of MATR3, exhibited increased alternative splicing specifically in the hippocampus of male offspring. Conclusions This study provides the first evidence that prenatal BPA exposure disrupts the alternative splicing and transcriptional regulation of ASD-related genes in offspring’s hippocampus in a sex-specific manner. These disruptions, particularly the YY1-mediated regulation of Matr3 and downstream effects on Agap1 splicing in males, offer new insights into the molecular mechanisms by which BPA may contribute to ASD pathogenesis.